Influence of AB0-incompatibility on complications occurrence after allogeneic hematopoietic stem cell transplantation - M. A. Kucher; M. A. Estrina; S. N. Bondarenko; N. E. Ivanova; A. L. Alyansky; B. V. Afanasyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Research objective: To assess the impact of AB0 erythrocyte antigens system incompatibility on complications incidence after allogeneic hematopoietic stem cell transplantation (alloHSCT). Patients and methods. The study included 240 patients - recipients for alloHSCT with oncological and hematological diseases. The median age was 19.0 (1-66) years. The research revealed that overall incidence of acute graft-versus-host disease (aGVHD) was higher in the case of AB0-incompatibiIity (p